Perubahan Preferensi Menonton Film pada Era Media Sosial: Dampak Short Video dan Implikasinya pada Perilaku Menonton Film - Verakandhi, Diyah (Institut Seni Indonesia Yogyakarta, 2024)
This research investigates changes in film viewing preferences in the context of the social media era. The main focus of the research is the impact of short videos reviewing films and their implications for film watching behavior. In the face of dramatic changes in film accessibility and the influence of social media, this research seeks to understand how short videos, especially those containing spoilers, influence the way viewers enjoy and appreciate films. The research method used is a mixed method, namely qualitative and quantitative involving surveys, short video content analysis, and interviews with film producers and directors. The findings of this research illustrate significant changes in film viewing preferences and their implications for the way audiences explore and enjoy film works. This research provides in-depth insights into the transformation of film viewing behavior in the dynamic social media era and proposes recommendations that can be useful for the film industry and social media content creators.